Cases and Concepts in Occupational Adaptation : Translating Theory into Action. - Evetts, Cynthia Lee.; Baxter, Mary Frances ([Place of publication not identified] : Routledge, 2024)
Timely and updated to reflect the Occupational Therapy Practice Framework: Domain and Process, Fourth Edition (OTPF-4), Cases and Concepts in Occupational Adaptation: Translating Theory into Action contains all the pertinent information regarding occupational adaptation theory combined into one easy-to-digest textbook. Cases and Concepts in Occupational Adaptation: Translating Theory into Action expands upon the groundwork laid in Janette K. Schkade and Melissa McClung's Occupational Adaptation in Practice: Cases and Concepts while leaving behind the workbook format in favor of an anthology focused on occupational adaptation theory, its history, and growth. Twenty years of research utilizing occupational adaptation theory is used in the text to show evidence of the use of theory in practice. What's included in Cases and Concepts in Occupational Adaptation: The original "Try It On" component plus four additional worksheets to promote application and critical thinking Real-world clinical case reports and new practice models demonstrating how to use occupational adaptation theory across the life span, in various practice settings, and influencing systems or environments Neuroscience foundations that support the constructs of the theory and its use in practice Perfect for entry-level occupational therapy students in master's or clinical doctoral programs, postprofessional students seeking to expand their theoretical repertoire, and practicing therapists who wish to ground their practice in theoretical constructs, Cases and Concepts in Occupational Adaptation: Translating Theory into Action stays true to the original while showcasing the changes to occupational adaptation theory from the past 20 years.
1. Overview of the Occupational Adaptation Theory: What's Occupational Adaptation?2. Desire for Mastery, Demand for Mastery, Press for Mastery: How Do the Person and the Environment Relate?3. Occupational Challenge, Internal and External Expectations, Person, and Occupational Environment: Where Do Occupational Role Expectations Fit?4. Adaptive Response Generation, Adaptive Response Mechanism: How Does the Person Begin to Produce the Response?5. Adaptation Gestalt: What's the Plan to Carry Out the Response?6. Adaptive Response Evaluation, Relative Mastery: What's Going on Here?7. Adaptive Response Integration, Adaptive Repertoire: How Has the Person Changed or Adapted?8. Assessment by the Occupational Environment, Incorporation into the Occupational Environment: How Does the Environment Respond?9. Assessment and Measures: How Can We Tell Adaptation Is Needed or Occurred?10. Intervention Tools, Therapist as Agent of the Environment, Client as Agent of Change: What Does the Therapist Do?11. Documentation and Dissemination, Interprofessional and Intraprofessional Communication: How Do You Describe Occupational Adaptation to Others? Occupational Adaptation Practice Models12. Practice Models Highlighting Occupational Adaptation Across the Life Span13. Setting-Specific Occupational Adaptation Practice ModelsAppendix A: Janette K. Schkade on Adaptive CapacityAppendix B: Worksheet Answer Keys
Keywords: MEDICAL / Allied Health Services / Occupational Therapy